Impact of media messages on containment of Coronavirus pandemic in Nigeria - Sunday G. John (AOSIS, 2023)
Background: Different countries adopted various measures to stop the spread of COVID-19. In Nigeria, the federal government, through the Presidential Task Force on the pandemic and some non-governmental organizations, mounted vigorous public enlightenment and education campaign through the media to contain the spread of the disease. Objective: This article examined the impact of that effort by assessing the level of public awareness, perception, and satisfaction the campaign generated. Method: A cross-sectional design and purpose sampling tech- nique were used for the study. Questionnaires were distributed online through personal and group platforms on Whatsapp and Telegram applications. This technique ensured that only the users of these applications responded to the questionnaire. The national survey returned 359 responses. Results: The results indicated a high level of public awareness from the media messages as 89.08% of respondents heard about COVID-19 from the media messages, 87.74% believed that media messages about the pandemic increased their awareness of it and 90.81% of respondents got influenced by the media messages to adjust to safety protocols against the disease. Majority of the respondents (75.49%) were satisfied with the overall performance of the media in their sensitization campaign. While 49.03% benefitted to a very large extent from the media messages, 44.01% benefitted to a large extent. Conclusion: The results showed that the impact of the media awareness messages on COVID-19 was high and that Nigerian media contributed immensely to reducing the spread of the disease in the country.